Detection and functional assessment of structural variants using whole genome re-sequencing data in Nellore cattle - Marin-Gazon, Natália Andrea (2023)
Ongoing advances in genome sequencing technologies have enabled the unravelling of many structural variants (SVs) in livestock genomes. Association of SVs with complex traits are promising targets for animal breeding because of their effects on gene expression. The aims of this study were: i). to detect structural variants using whole genome resequencing data of 151 representative Nellore bulls by combining calling algorithms ii) to discover non redundant and highly frequent regions of structural variants (SVR) in the analyzed bulls. iii). to search for positional candidate genes, and quantitative trait loci (QTL) overlapping the most frequent SVR in the population. iv) to assess the functional impact of positional candidate genes overlapping SVR trough enriched gene ontology terms (GO terms) related to biological process (BP), molecular function (MF), cellular component (CC), and biochemical pathways. The whole genome re-sequencing (WGS) data from 151 representative Nellore bulls was used to conduct genome-wide structural variation calling, as well as detection of common SVRs for the analyzed bulls. The gene content and nearby QTLs of SVRs were retrieved from publicly available genomic databases, and functional enrichment analysis of positional candidate genes overlapping the most frequent SVRs were conducted using PANTHER. A total of 215,031 high-confidence SV was obtained, most of them corresponding to copy number variants (CNV) (183,032 deletions-DEL, and 14,013 duplications-DUP), and 17,986 inversions (INV). Total structural variation encompasses, on average, 4.81% of the individual autosomal genome extension. A total of 3,752 non-redundant SVR frequent in more than 5% of bulls were obtained, corresponding in more than 97% to regions of copy number variants (CNVR), and 3% to regions of inversions (INVR). All SVR comprises 13.13% of total autosomal genome extension, which were attributed in 11.4% to CNVR and 1.7% to INVR. Among all SVRs, 532 were shared by more than 50% of bulls and overlapped a total of 130 QTL distributed into 6 QTL types: exterior, health, meat and carcass, milk, production, and reproduction, which are related to a total of 50 economically important traits. Most SVR overlapped QTLs related to residual feed intake, structural soundness, multiple birth, clinical mastitis, and milk energy yield. Regarding gene content, 204 SVRs, overlapped a total of 1,164 positional candidate genes, which were significatively overrepresented into GO terms related to BP, MF, CC and one biochemical pathway. Among the significantly enriched genes, we highlight members of the olfactory receptor (OR) gene family, which play essential roles in mechanisms for adaptation to the environment. These genes were mainly found into regions of inversion and mixed events. Similarly, genes from the defensin family (DEFB), that play important roles in the innate immune system of multicellular organisms, and which are known to be caused by duplication events that mammalian genomes have undergone. Other important genes were found in this study, such as the members of the secretory phospholipase A2 family, adhesion G protein-coupled receptors, and zinc finger binding proteins. Most of the genes found in this study have been described as potential candidates for feed efficiency indicator traits, which reflects the biochemical mechanisms in which they are involved that have led to the improved fitness. The results of this study provide important knowledge about the mechanisms driving changes in the genome in Nellore cattle, the contributed to adaptation to environment.